Inflasi dan Suku Bunga terhadap Return Saham Subsektor Perbankan Indeks KOMPAS100 2015 – 2019 - Nanna Sugiyanto, Fransiskus Xaverius; Nazar, Shinta Ningtiyas; Syafrizal, Kansas (E-Jurnal Akuntansi; Vol 31 No 6 (2021)DO - 10.24843/EJA.2021.v31.i06.p20, 2021)
The consider pointed to decide & to demonstrate experimentally the impact of swelling & intrigued rate on the stock return of the keeping money subsector stock within the KOMPAS100 record. Analyst utilized control factors, to be specific PER & PBV. This sort of investigate classified as quantitative inquire about & utilizing auxiliary information. The populace in this study are stocks within the KOMPAS100 record 2015-2019 & utilized purposive testing strategy coming about 9 stocks of the keeping money subsector of KOMPAS100 list 2015-2019 as the test. The examination method utilized in this inquire about is numerous straight relapse. The comes about demonstrate that the expansion & intrigued rate factors at the same time impact stock return with PER & PBV as control factors. The expansion variable does not have a significant effect on stock returns. Intrigued rate variable incorporates a critical negative impact on stock returns. PER & PBV as control factors have no critical impact on stock return. Keywords: Inflation; Interests; Stock Return; Indeks KOMPAS100.